MANAGEMENT OF SPORTING EVENTS AS AN INSTITUTIONAL ENGAGEMENT STRATEGY (International Seven Journal of Multidisciplinary, 2025)
The study explored how the management of sporting events has been consolidating in Brazil as a strategy for institutional engagement, generation of symbolic value and strengthening of brands. The analysis brought together contributions from national authors who address planning practices, sponsorship activation, sustainability and legacy building in competitions of different sizes. It was observed that the adoption of structured methodologies, combined with operational flexibility, has enhanced results and provided significant experiences to different audiences. It was also found that the emotional dimension of sport exerts a decisive influence on the social perception of the initiatives, creating opportunities for companies to associate their brands with positive values, such as overcoming and collective belonging. At the same time, challenges persist related to transparency in the management of resources, the assessment of long-term impacts, and the encouragement of the democratic use of the infrastructures created. The work highlighted that the success of an event depends on a balanced combination of professionalism, technological innovation and genuine attention to social demands. It was found that even projects with a lower budget can generate relevant changes when they articulate clear objectives and communication strategies that dialogue with the interests of the community. The discussion also revealed that institutional credibility is strengthened when sustainability and social responsibility practices are integrated into the planning and execution of actions. Building lasting legacies requires organizations to develop a systemic vision and cultivate relationships based on trust and ethical commitment. These factors, combined with the continuous investment in the formation of qualified teams, represent possible ways for sport to assert itself as an engine of cultural and economic development.